Investigating the Effectiveness of Kahoot Quizzes in Grammar Learning - Alawiyah, Rosidah; Elthia, Memy Wardani; Tanashur, Panji (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This research investigates the effectiveness of Kahoot, a game-based learning platform, in enhancing motivation for learning grammar among university students. Recognizing the challenges faced by non-native English speakers in mastering grammar, the study explores the potential of gamification as an innovative teaching approach. A survey method was employed to collect data from 10 English university students using both structured and unstructured questionnaires. The findings reveal that Kahoot significantly enhances student motivation, engagement, and enjoyment in learning grammar. Students report higher satisfaction and improved understanding of grammar concepts compared to traditional teaching methods. However, the study highlights challenges, such as increased anxiety due to the competitive atmosphere and technical issues like internet connectivity. These results suggest that while Kahoot is an effective tool for grammar instruction, careful implementation is required to address its limitations and optimize its effectiveness. This research offers valuable insights for educators and researchers seeking to harness technology to improve grammar learning outcomes